Pengembangan Media Pembelajaran Bahasa Arab Berbasis Artificial Intelligence untuk Siswa Kelas V - Nurul Atika; Saepudin Saepudin; Hamsa Hamsa; Herdah Herdah; Darmawati Darmawati (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to develop an artificial intelligence–based Arabic language learning medium suitable for fifth-grade elementary school students. The research employed a research and development (R&D) approach using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The development process focused on using artificial intelligence to produce learning content by integrating Canva AI, Whisk, and Suno to create a web-based learning platform with visual, auditory, and interactive features. A limited trial was conducted with 18 fifth-grade students at SDIT Al-Insan Pinrang. Data were collected using validation sheets completed by material and media experts, as well as response questionnaires administered to students and teachers to assess the practicality of the developed media. The results indicated that the learning medium achieved a very high level of validity, with a score of 92% from the material expert and 88% from the media expert. Furthermore, the practicality test showed that the medium was categorized as very practical, with scores of 83% from students and 90% from teachers. These findings suggest that the developed media is feasible and practical for use as a supporting medium in Arabic language learning at the elementary school level. The novelty of this study lies in the use of artificial intelligence to produce Arabic learning content that integrates visual, auditory, and interactive elements within a single web-based platform, offering an innovative alternative for Arabic language learning in basic education.